AEK Kanopan Outer Urban Ring Road Plan In The Context Of Controlling The Volume And Capacity Of Roads In The District North Labuhanbatu - Deni Johanysah; Abdi Sugiarto; Cut Nuraini (CV. Doki Course and Training, 2026)
This study aims to analyze the influence of the development of the Aek Kanopan Outer Ring Road on traffic volume control on the main section of the city as well as the potential for regional development and economic activities around it. The research approach uses a qualitative case study method, with data collection through in-depth interviews, Focus Group Discussions (FGDs), field observations, and analysis of planning documents. The results of the study show that the main section of the city is currently experiencing moderate to high density (LOS C–D), so it requires current diversion intervention. The Outer Ring Road has significant potential as an alternative route for transit vehicles and heavy vehicles, which can reduce traffic load on the main section. In addition, increased accessibility along the track encourages the development of directional areas: the eastern region has potential as an industrial and warehousing region, while the western corridor has the potential to be a residential and local trade hub. Ring road optimization requires an integrated strategy including technical design, route arrangement, spatial integration, supporting facilities, and continuous monitoring. This study provides recommendations for local governments in planning and managing the Aek Kanopan Outer Ring Road as a traffic control solution as well as a driver of sustainable regional growth.